Analysing the social effects of tourism on residents: the case of Parys, South Africa - Sigo, N. E. (Vaal University of Technology, 2018)
Residents’ attitudes towards and opinions about tourism is important as they are the ones dealing directly or indirectly with tourists and the development of the industry. As one of the key stakeholders their support is needed to grow the industry in a sustainable manner. For South Africa as a developing country tourism is one of the focus areas of development. This growth is supported by a number of initiatives to create more (but also more sustainable) tourism destinations especially for small towns such as Parys (Free State; South Africa). The primary objective was to analyse the social effects of tourism and determine the factors influencing these effects on the local community of Parys, located in the province of the Free State. This was done by conducting an empirical study among residents in Parys. The questionnaire was developed based on similar research done in other communities. The questionnaires were captured in Microsoft Excel and analysed in the IBM Statistical Package for Social Sciences (SPSS v 23.0). From a negative point of view residents highlighted the increase in prices of goods and services due to tourism development. From a positive perspective residents felt that the development of tourism lead to more opportunities for people to have fun, more tourists visit the area and the image of Parys has improved. From the factor analysis for social effects the following factors were evident: Business and community effects, Negative social effects, Opportunities for residents, Environmental effects and Cost of living effects. The latter two factors were rated the highest and thus residents felt that tourism lead to an effect on the environment and an effect on their cost of living. This should be monitored so that residents remain positive and do not start to blame tourists for negativities happening in Parys. When analysing the image of Parys from the perspective of the residents the factor analyses revealed three factors namely Infra- and suprastructure, Nature and cultural attractions and Hospitality of which they felt the strongest about the first and the last factor. Clearly from the results these residents enjoy staying in Parys, do not consider tourists to be a threat and welcomes visitors to the area. The social effects of tourism development is, to a certain extent, influenced by gender, language, level of education, age and number of years living in Parys. Overall it can be concluded that residents are fairly happy with tourists visiting Parys and the development taking place due to tourism. They are aware of the negative impacts but the positive impacts currently outweigh the negative impacts. It is recommended to include residents in the development process or at least keep them aware of what is happening, why it is happening and what opportunities it might bring to them. The results of this study differ from that of others indicating that communities are unique and there are unique aspects influencing their opinions regarding the social effects of tourism. The researcher recommended that the private and public sectors of Parys should continue their current practices to uphold the positive attitudes but also consider options where residents can become more involved in the development of the industry.
M. Tech. (Department of Tourist and Hospitality Management: Tourism Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Social impacts/effects; Tourism industry; Sustainable tourism development; Tourism -- Management.; Tourism -- Developing countries.; Sustainable tourism.; Community development -- Social aspects.; Dissertations, Academic -- South Africa.